Statins and their impact on epigenetic regulation: insights into disease - Tamayo-Trujillo, Rafael; Guevara-Ramírez, Patricia; Cadena-Ullauri, Santiago; Ruiz Pozo, Viviana A.; Paz-Cruz, Elius; Zambrano, Ana Karina (Frontiers in Pharmacology, 2025)
Statins have been primarily used for the management of low-density lipoprotein cholesterol and cardiovascular diseases However, in recent years, research has identified potential applications beyond cholesterol regulation. Statins exhibit pleiotropic effects, due to their ability to modulate gene expression via epigenetic mechanisms, including DNA methylation, histone acetylation, and microRNA regulation. Clinical studies have correlated these epigenetic changes with various pathological conditions, such as inflammation, atherosclerosis, cancer, diabetes, and autoimmune disorders. Despite encouraging findings, further research is required to fully understand the molecular pathways associated with the epigenetic actions of statins and disease pathogenesis. This review describes the potential role of statins as epigenetic modulators and their relevance in human disease management.